Green synthesis of Zeolitic Imidazolate Framework (ZIF) nanoparticles for theranostics - Loo, Yan Shan; Silvaraju, Gaayatri; Nur Airin Syahira, Johari; Nur Aininie, Yusoh; Afiq, Azil; Norazalina, Saad; Mohd Basyaruddin, Abdul Rahman; Nurul Akmarina, Mohd Abdul Kamal (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2025)
Metal–organic frameworks (MOFs) are crystalline materials composed of organic linkers and inorganic nodes. These structures typically exhibit ultra-high surface areas, ranging between 1000 and 7000 m2/g, and tunable pore sizes and volumes, which are ideal characteristics for therapeutic uses. Zinc imidazolate frameworks (ZIFs) have gained recognition in recent studies as a promising candidate for on-demand drug delivery due to their high loading capacity, stability in physiological conditions, and controllable drug release properties. However, the use of ZIFs for in vivo applications requires a clear understanding of their interaction with biological tissues and a comprehensive evaluation of biocompatibility, a key consideration in improving their clinical translatability. In this review, an overview is provided on green synthesis approaches for the preparation of ZIFs from their inorganic base materials, by employing naturally-derived reaction components, sustainable alternative reaction media, or eco-friendly processes. The link between green-synthesized ZIFs and their concomitant performance in therapeutic/theranostic applications has not been extensively explored. However, nanoparticles developed by sustainable/green routes often demonstrate lower toxicity and improved biocompatibility, necessary for therapeutic/theranostic uses. Recent developments in green-synthesized ZIFs underscore their multifaceted role in enhancing biocompatibility and bioavailability, targeted delivery, and/or theranostic performance at the targeted disease site.